Predicting axillary nodal metastasis based on the side of asymmetrical cortical thickening in breast cancer: Evaluation with grayscale and microvascular imaging findings. Issue 158 (January 2023) - Aladag Kurt, Seda; Kayadibi, Yasemin; Onur, Irem; Uslu Besli, Lebriz; Necati Sanli, Ahmet; Velidedeoglu, Mehmet
Highlights: Side of the cortical asymmetry (closer or distant to breast), cortex/hilum ratio and abnormal vascularisation pattern are independent predictors of axillary metastasis. Closer asymmetrical enlargement in ALNs is a significant simple finding in predicting metastases. In ALNs with asymmetrical cortical enlargement, the side of the thickening (closer or distant asymmetry), the vascular pattern on Doppler US, and, if present, the FDG uptake in PET scan, can be used to decide on sampling. Abstract: Purpose: To investigate the relationship between sonographic findings and the axillary status, especially the side of thickening in the presence of cortical asymmetry. Methods: Patients with biopsy-proven axillary lymph node (ALN) metastasis were included in this study. The lymph nodes were divided into three groups depending on the type of cortical thickening as diffuse, closer (eccentric cortical thickening on the side near the tumor and/or breast) and distant (thickening on the further side) asymmetry. Longitudinal to transverse axis (L/T) ratio, the largest cortical thickness, cortex to hilum ratio (C/H), hilar status (normal/displaced/absent), orientation (parallel/vertical), capsular integrity (sharp/indistinct), vascularisation pattern (hilar/peripheral/penetrant/anarchic/avascular) on superb microvascular imaging (SMI) and presence of conglomeration were recorded for each lymph node. Axillary nodal status on 18 F-FDG PET-CT/MRI scans was recorded, if available. Features of the breast lesions like size, laterality, nuclear grade, hormone receptor status and the level of Ki-67 expression have been added. Results: A total of 219 metastatic ALNs [diffuse (n = 122), closer asymmetry (n = 71), distant asymmetry (n = 26)] were evaluated. By the univariate analysis, ALN metastasis was significantly associated with the presence of closer asymmetrical cortical thickening (p < 0, 0001), C/H ratio (p = 0.001), cortical thickness (p = 0.001), hilar status (p < 0.005) and vascular pattern (p < 0.005). L/T ratio was only a statistically significant parameter for lymph nodes with diffuse cortical enlargement in predicting metastasis, and conglomeration was also observed only in this group (p < 0.05). By multivariate analysis, nodal metastasis was significantly associated with asymmetrical cortical thickening (p = 0.001), C/H ratio (p = 0.005) and vascular pattern (p < 0.0001). Conclusion: Asymmetrical cortical enlargement on the side closer to the breast, C/H ratio and abnormal microvascular pattern are the independent predictors of axillary nodal involvement. Closer asymmetry is an eligible, easy-to-detect grayscale US finding to decide sampling that highly predicts ALN metastasis.